Apolipoprotein E gene variants shape the association between dietary fibre intake and cognitive decline risk in community-dwelling older adults. (27th January 2023) - Unión-Caballero, Andrea; Meroño, Tomás; Andrés-Lacueva, Cristina; Hidalgo-Liberona, Nicole; Rabassa, Montserrat; Bandinelli, Stefania; Ferrucci, Luigi; Fedecostante, Massimiliano; Zamora-Ros, Raúl; Cherubini, Antonio
Abstract: Background: healthy dietary patterns have been associated with lower risk for age-related cognitive decline. However, little is known about the specific role of dietary fibre on cognitive decline in older adults. Objective: this study aimed to examine the association between dietary fibre and cognitive decline in older adults and to assess the influence of genetic, lifestyle and clinical characteristics in this association. Design and participants: the Invecchiare in Chianti, aging in the Chianti area study is a cohort study of community-dwelling older adults from Italy. Cognitive function, dietary and clinical data were collected at baseline and years 3, 6, 9 and 15. Our study comprised 848 participants aged ≥ 65 years (56% female) with 2, 038 observations. Main outcome and measures: cognitive decline was defined as a decrease ≥3 units in the Mini-Mental State Examination score during consecutive visits. Hazard ratios for cognitive decline were estimated using time-dependent Cox regression models. Results: energy-adjusted fibre intake was not associated with cognitive decline during the 15-years follow-up ( P > 0.05). However, fibre intake showed a significant interaction with Apolipoprotein E (APOE) haplotype for cognitive decline ( P = 0.02). In participants with APOE-ɛ4 haplotype, an increase in 5 g/d of fibre intake was significantly associated with a 30% lower risk for cognitive decline. No association was observed in participants with APOE-ɛ2 and APOE-ɛ3 haplotypes. Conclusions and relevance: dietary fibre intake was not associated with cognitive decline amongst older adults for 15 years of follow-up. Nonetheless, older subjects with APOE-ɛ4 haplotype may benefit from higher fibre intakes based on the reduced risk for cognitive decline in this high-risk group.